Evaluating walkability across age groups and flooring materials using IMU sensors - Jo, Daehwi; Kim, Hyunsoo (Frontiers in Public Health, 2024)
This study presents a novel approach to quantitatively assess the impact of flooring materials on walkability using Inertial Measurement Unit (IMU) sensors and Dynamic Time Warping (DTW) algorithm. Four common pavement materials (wood, asphalt, concrete block, and cement) were evaluated across five age groups (20–30, 30–40, 40–50, 50–60, and over 60 years) with 80 participants walking 1,200 m on each surface. IMU sensors attached to the lumbar region recorded acceleration and gyroscope data, which were then analyzed using DTW to quantify gait stability. Results showed significant differences in DTW values among materials, with wood exhibiting the lowest average DTW value (12.99 ± 3.05) indicating the most stable walking environment, while cement showed the highest (39.14 ± 9.74). In addition, age-related analysis revealed increasing DTW values with age across all materials, with the most pronounced effect in the older adult group. The methodology presented offers sensor-based approach for evaluating and optimizing pedestrian infrastructure in smart city development.